2006
DOI: 10.1111/j.1468-3148.2006.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Service User Outcomes of Staff Training in Positive Behaviour Support Using Person‐Focused Training: A Control Group Study

Abstract: Background Effectively supporting individuals with intellectual disabilities who display challenging behaviours continues to be a priority for service providers. Personfocused training (PFT) is a model of service delivery which provides staff with skills in functional assessment and intervention development. Existing longitudinal data from a study of 138 cases suggest that implementation of staff-developed behaviour support plans through PFT is effective in reducing challenging behaviour in approximately 77% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 22 publications
5
54
0
Order By: Relevance
“…McClean et al (2005) analysed data from 138 staff-developed behaviour support plans over a 5-year period and observed signifi cant improvements in 77% of cases (defi ned as a reduction to below 30% of baseline rates of behaviour) and that at an average follow-up of 22 months such improvements were maintained. In a control group study, Grey and McClean (2007) observed similar improvements in a target group of clients but not in a matched control group of clients over a 6-month period, lending further support to the effi cacy of PFT.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…McClean et al (2005) analysed data from 138 staff-developed behaviour support plans over a 5-year period and observed signifi cant improvements in 77% of cases (defi ned as a reduction to below 30% of baseline rates of behaviour) and that at an average follow-up of 22 months such improvements were maintained. In a control group study, Grey and McClean (2007) observed similar improvements in a target group of clients but not in a matched control group of clients over a 6-month period, lending further support to the effi cacy of PFT.…”
supporting
confidence: 58%
“…However, there is little evidence to support such an argument. A previous control group study (Grey & McClean, 2007) tracked the effectiveness of PFT against a control group of individuals with similar challenging behaviours. Levels of psychotropic medication were very similar in both groups with only the PFT group showing changes in measures of challenging behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training staff in behaviour management skills, positive behaviour supports and communication training programmes have resulted in reduced use of restraints (Allen et al. 1997; Grey & McClean 2007; Smidt et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, DSWs appear to benefit from meaningful supervision and managerial support to assist them in applying new learning (e.g., Grey & McClean, 2007;Stancliffe, Harman, Toogood, & McVilly, 2007). Johnson, Iacono, Hagiliassis, and Phillips (2010) found that DSWs desired such input from senior staff.…”
Section: Potential Support Strategiesmentioning
confidence: 96%